Environmental factors shaping boring sponge assemblages at Mexican Pacific coral reefs. (16th October 2012) - Nava, Héctor; Carballo, José Luis
Abstract Recent studies suggest a future increase in sponge bioerosion as an outcome of coral reef decline around the world. However, the factors that shape boring sponge assemblages in coral reefs are not currently well understood. This work presents the results of a 17‐month assessment of the presence and species richness of boring sponges in fragments collected from living corals, dead coral reef matrix and coral rubble from Punta de Mita and Isabel Island, two coral reefs from the central coast of the Mexican Pacific Ocean. Both localities have a high cover of dead corals generated by past El Niño Southern Oscillation events, but Punta de Mita was also highly exposed to anthropogenic impacts. Additionally, environmental factors (water transparency, water movement, temperature, sediment deposition, SST, and chlorophyll concentration) were assessed to test the hypothesis that environmental conditions which are potentially harmful for corals can enhance sponge bioerosion. Isabel Island and Punta de Mita showed a similar species richness (13 and 11 species, respectively) but boring sponge presence in both live and dead corals was higher at Isabel Island (57.6%) than at Punta de Mita (35.7%). The same result was obtained when each type of substrate was analysed separately: dead coral reef matrix (81.3% versus 55.5%), coral rubble (47.7% versus 20.0%) and living corals (43.7% versus 31.7%). A principal components analysis showed a higher environmental heterogeneity at Punta de Mita, as well as important environmental differences between Punta de Mita and Isabel Island, due to sediment deposition (2.0 versus 0.2 kg·m−2·d−1) and water movement (24.5% versus 20.5% plaster dissolution day−1), that were also negatively correlated with boring sponge presence (r = −0.7). By analysing the boring sponge assemblage, we found that environmental settings, together with habitat availability (i.e., dead coral substrate) differentiated assemblage structure at both localities. Major structural differences were largely due to species such as Cliona vermifera, Cliona tropicalis and Aka cryptica. In conclusion, factors such as habitat availability favored the presence of boring sponges but some environmental factors such as abrasion resulting from moving sediment acted restrictively, and exerted a major role in structuring boring sponge assemblages in the Mexican Pacific.